PENGARUH LATIHAN SKIPPING TERHADAP HASIL TENDANGAN JARAK JAUH SEPAK BOLA DI SSB NEW STAR FA SEMARANG - Alip Fajar; Anggit Wicaksono (Universitas Negeri Semarang, 2023)
The background in this study is the lack of quality long-range kicks in soccer games. This study aims to determine the effect of Skipping exercises on the results of the ability to shoot long distance SSB NEW STAR FA players. This study used an experimental method with a pre-test and post-test group design. The population of this study were 20 SSB NEW STAR FA players. The sampling technique is purposive sampling. The sample of this research is 10 SSB NEW STAR FA Semarang players. Based on the results of the study, it was shown that there was a significant effect of Skipping exercises on the long-range kick results of SSB NEW STAR FA players. The conclusion is that there is an effect of Skipping exercises on the results of long distance kicks in soccer at SSB NEW STAR FA Semarang. Suggestions for players to improve the quality of long distance kicks can be used with Skipping exercises.